Development of in situ PCR technique for detection of very virulent infectious bursal disease virus strain - Elawad, H. A.; Bejo, Mohd Hair; Omar, Abdul Rahman; Arshad, Siti Suri; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A very virulent infectious bursal disease virus (vvIBDV) strain (UPM0081) was inoculated orally in 4-week-old specific pathogen free (SPF) chickens. Control was included and these chickens were not inoculated with the virus. The chickens in both groups were sacrificed at various intervals and samples of bursa of Fabricius, caecal tonsils, liver, spleen and kidney were fixed in 10% buffered formalin, processed and embedded in wax. A digoxigenin-labeled probe was designed according to the sequence of VP2 gene (vvIBDV). By application of in situ PCR technique, the probes were evaluated as a marker of the gene and to subsequently detect the presence of the virus. The technique was carried out on tissues of organs collected at 24, 48, 72, 96 and 120 hours post-inoculation (pi). The virus was detected in all samples at all times of sampling. The virus was not detected in all samples from the control group. It was concluded that this study has successfully developed an in situ PCR technique for detection of vvIBDV by formation of specific probes complementary to VP2 gene.